CLINICAL FEATURES OF STRANGE WITH OVERACTIVITY OF THE LOWER CROSS MUSCLE AT THE CENTRAL EYE HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the clinical characteristics of strabismus with inferior oblique muscle overactivity at the National Eye Hospital in 2025.Subjects and methods: Cross-sectional descriptive study on children under 16 years old diagnosed with strabismus with inferior oblique muscle overactivity detected at the National Eye Hospital from April 1, 2025 to October 31, 2025.Results: There were 48 patients with 69 eyes meeting the research criteria. The average age was 7.35 ± 3.76; the youngest was 2 years old, the oldest was 16 years old. The prevalence of males was 47.9%, and females was 52.1%. Assessing the amblyopia status, there were 32 eyes (56.1%) without amblyopia, 12 eyes (21.1%) with mild amblyopia, 11 eyes (19.3%) with moderate amblyopia, and 2 eyes (3.5%) with severe amblyopia. Binocular vision was present in 12 patients (33.3%), and binocular vision was absent in 24 patients (66.7%). The degree of lower cross-linking hyperactivity was commonly found at level 2+ in 58%, level 1+ in 18.8%, level 3+ in 21.8%, and level 4+ in 1.4%. Vertical strabismus below 10 PD accounted for 13.1%, 10-20 PD accounted for 80.4%, and > 20 PD accounted for 6.5%. Most patients with lower cross-linking hyperactivity had associated strabismus forms, including internal strabismus in 29.2%, external strabismus in 35.4%, V-shaped syndrome in 4.2%, DVD syndrome in 4.2%, and no combined strabismus form accounted for 29.2%.Conclusion: Inferior oblique hyperactivity is a common ocular motility disorder, most commonly grade 2+, 3+ inferior oblique hyperactivity with vertical strabismus from 10-20 PD and often combined with other forms: internal strabismus, external strabismus, V-shaped syndrome, DVD. Therefore, when treating, it is necessary to pay attention to finding the combined strabismus forms.
Keywords: Inferior oblique hyperactivity, strabismus, clinical features.